Membantu Masyarakat Mencegah Wabah Covid-19 - Wiwik Indrawati (UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe Covid-19 pandemic outbreak has become a frightening ghost for the entire world community, including the people of Indonesia. Therefore, prevention and self-protection efforts are carried out by community members by keeping a distance, not crowding, maintaining endurance, maintaining cleanliness, and doing disinfection in the home, environment and public places. In this case the University of Pamulang through the Chemical Engineering Study Program carried out disinfection movements in several areas in Pamulang, in order to prevent the spread of the Covid-19 virus.Keywords: Covid-19, Society, Disinfection AbstrakWabah pandemi Covid-19 telah menjadi hantu yang menakutkan bagi seluruh masyarakat dunia, termasuk masyarakat Indonesia. Oleh karenanya, dilakukan upaya pencegahan dan perlindungan diri oleh warga masyarakat dengan cara menjaga jarak, tidak berkerumun, menjaga daya tahan tubuh, menjaga kebersihan, dan melakukan disinfeksi di rumah, lingkungan serta tempat umum. Dalam hal ini Universitas Pamulang melalui Prodi Teknik Kimia melakukan gerakan disinfeksi pada beberapa wilayah di Pamulang, guna mencegah penyebaran virus Covid-19.Kata Kunci: Covid-19, Masyarakat, Disinfeksi